The availability of global guidance for the promotion of women's, newborns', children's and adolescents' health and nutrition in conflicts. (22nd November 2020) - Aboubaker, Samira; Evers, Egmond Samir; Kobeissi, Loulou; Francis, Lauren; Najjemba, Robinah; Miller, Nathan P; Wall, Steve; Martinez, Daniel; Vargas, Joseph; Ashorn, Per
Abstract : Background: Significant global gains in sexual, reproductive, maternal, newborn, child and adolescent health and nutrition (SRMNCAH&N) will be difficult unless conflict settings are adequately addressed. We aimed to determine the amount, scope and quality of publically available guidance documents, to characterise the process by which agencies develop their guidance and to identify gaps in guidance on SRMNCAH&N promotion in conflicts. Methods: We identified guidance documents published between 2008 and 2018 through English-language Internet sites of humanitarian response organisations, reviewed them for their scope and assessed their quality with the AGREE II (Appraisal of Guidelines for REsearch and Evaluation II) tool. Additionally, we interviewed 22 key informants on guidance development, dissemination processes, perceived guidance gaps and applicability. Findings: We identified 105 conflict-relevant guidance documents from 75 organisations. Of these, nine were specific to conflicts, others were applicable also to other humanitarian settings. Fifteen documents were technical normative guidelines, others were operational guides (67), descriptive documents (21) or advice on legal, human rights or ethics questions (2). Nutrition was the most addressed health topic, followed by communicable diseases and violence. The documents rated high quality in their 'scope and purpose' and 'clarity of presentation' and low for 'rigour of development' and 'editorial independence'. Key informants reported end user need as the primary driver for guideline development and WHO technical guidelines as their main evidence base. Insufficient local contextualisation, lack of inter-agency coordination and lack of systematic implementation were considered problems in guideline development. Several guidance gaps were noted, including abortion care, newborn care, early child development, mental health, adolescent health beyond sexual and reproductive health and non-communicable diseases. Interpretation: Organisations are motivated and actively producing guidance for SRMNCAH&N promotion in humanitarian settings, but few documents address conflicts specifically and there are important guidance gaps. Improved inter-organisation collaboration for guidance on SRMNCAH&N promotion in conflicts and other humanitarian settings is needed.